Thematicity in English academic research articles across disciplines in hard and soft sciences - Ebrahimi, Seyed Foad (2014)
Theme which is defined as the starting point of the message and the element which the clause is mainly about plays a major role in text organization (Halliday, 1994). This study explores the types and discourse functions of theme in the research articles and its four rhetorical sections (introduction, method, result and discussion) across four disciplines: Applied Linguistics and Psychology representing soft science and Chemistry and Environmental Engineering representing hard science. This cross-disciplinary study was carried out on a corpus of 40 (10 from each discipline) research articles. The research articles sourced from 12 ISI journals (3 from each discipline) published from 2008 to 2012. The corpus was analyzed based on the modified model of the available models in relation to theme types and discourse functions. The results revealed that the theme type selections were guided by the nature of the rhetorical sections of the research article. However, the frequency of use of the theme types was constrained by the nature of the discipline. Discourse functions in relation to theme types were predominantly determined by the divisions of the hard and soft sciences, the specific disciplines within, and the internal structure of the rhetorical sections of the research articles. In addition, the results of this study manifest a new framework for the analysis of discourse functions of theme types in research articles. The results and analysis establish that the theme is an important means of highlighting the disciplinary variations in the writing of the rhetorical sections of the research article. The study has implications for novice research article writers, EAP instructors and EAP text developers. These results could be used to target at the awareness of linguistic features such as theme as a crucial element in dispensing of discourse functions of the rhetorical sections of the research article.